Resuscitation from a pH of 6.5: A Case Report and Review of Pathophysiology and Management of Extreme Acidosis from Hypovolemic Shock after Trauma - Alexander Balmaceda; Sona Arora; Ilan Sondheimer; McKenzie M. Hollon (Journal of Trauma and Injury)
Extreme acidosis is a life-threatening physiological state that causes disturbances in the cardiovascular, pulmonary, immune, and hematological systems. Trauma patients commonly present to the operating room (OR) in hypovolemic shock, leading to tissue hypoperfusion and the development of acute metabolic acidosis with or without a respiratory component. It is often believed that trauma patients presenting to the OR in severe metabolic acidosis (pH <7.0) will have a nearly universal mortality rate despite aggressive resuscitation and damage control. The current literature does not include reports of successful resuscitations from a lower pH, which may lead providers to assume that a good outcome is not possible. However, here we describe a case of successful resuscitation from an initial pH of 6.5 with survival to discharge home 95 days after admission with almost full recovery. We describe the effects of acute acidosis on the respiratory and cardiovascular systems and hemostasis. Finally, we discuss the pillars of management in patients with extreme acute acidosis due to hemorrhage: transfusion, treatment of hyperkalemia, and consideration of buffering acidosis with bicarbonate and hyperventilation.